Shrimp cephalothorax meal in laying hen diets. - Salas-Durán, Catalina; Chacón-Villalobos, Alejandro; Zamora-Sánchez, Laura (Agronomía Mesoamericana, 2015)
The aim of this study was to meassure the effect of shrimp meal (SM) in commercial laying hen diets. From April to September 2013, in Costa Rica, Pleuroncodes planipes was used to obtain a meal (SM) with a yield of 15%, particle size of 256 μg and negative for Salmonella sp. Proximate analysis was performed to the SM: crude protein (40.67%), ether extract (11.05%), crude fiber (7.12%), ash (27.48%), calcium (9.03%), phosphorus (2.66%), amino acid profile, pepsin digestibility (84%) and acidity (8.34). Subsequently, a trial was performed with 140 40-week-old Hy-Line Brown laying hens, fed with four different diets containing increasing levels of inclusion of SM (0%, 5%, 10%, and 15%) during four weeks; and formulated according to the ideal protein and digestible amino acids concepts; being isocaloric and isoproteic. The variables experimentally evaluated were: production percentage, feed intake, body weight, mortality, egg weight and feed conversion ratio. Only egg weight changed significantly between treatments in the third week (p<0.05). The hens fed with 5% SM laid heavier eggs. It is suggested to evaluate a level of SM inclusion up to 15% in laying hens diets.